P-016 Preliminary results of a multicenter study of endovascular and microsurgical treatment for 679 middle cerebral artery bifurcation aneurysms. (23rd July 2022) - Monteiro, A; Khawar, W; Kim, L; Levitt, M; Barros, G; Boulos, A; Paul, A; Jabbour, P; El Naamani, K; Nogueira, R; Haussen, D; Al Bayati, A; et al.
Abstract : Introduction: Though an increasing number of aneurysms have been treated with neurointervention in the last decades, those located at the middle cerebral artery bifurcation (MCAb) remained treated mostly with microsurgery. In the recent years, many new alternatives have been added to the endovascular armamentarium, and are yet to be directly compared. The current study is a multicenter experience of microsurgerical and endovascular treatment of MCAb aneurysms. Methods: Databases of 8 US centers were retrospectively reviewed. We included MCAb aneurysms treated with microsurgical clipping (MC), simple coiling (SC), stent-assisted coiling (SAC), flow-diversion (FD) and flow disruption (FDr; e.g Woven EndoBridge device). Characteristics of patients and aneurysms, complications, clinical and angiographic follow-up were extracted and compared among these groups. Results: 679 aneurysms were included (509 MCs, 20 FDs, 81 SCs, 47 SACs, and 25 FDrs). There were no differences in age, sex, and comorbidities. Mean aneurysm height and dome width were not different, but neck width was significantly larger (P=0.003 ) in the FD (3.32 mm). In unruptured aneurysms: intraoperative thromboembolic events, aneurysm rupture and vessel injury were not significantly, but SAC had significantly (P=0.004) higher rates of technical issues (10.3%); in-hospital complications and mortality were not different; thromboembolic complications during follow-up was significantly higher (P<0.001 ) in FD (21.1%); aneurysm rupture during follow-up was also significantly higher (P=0.02 ) in FD (5.3%). In ruptured aneurysms: intraoperative thromboembolic complication were significantly (P=0.003 ) higher in SAC (22.2%); intraoperative rerupture, vessel injury and technical issues were not different; the rate of in-hospital thromboembolic complications was significantly (P=0.029 ) higher in FDr (33.3%), while there was no difference in vasospasm and hemorrhagic events; in-hospital mortality was not different; there were no differences in thromboembolic events and rerupture during follow-up. Overall (ruptured and unruptured), median length of angiographic follow-up was significantly (P=0.03 ) longer in aneurysms treated with MC (22 months). Retreatment rate was significantly (P=0.002) higher in SC (15.6%). The rate of complete occlusion was significantly (P=0.01 ) higher in MC (80.6%). Conclusions: In this multicenter study of MCAb aneurysms, neck width and rupture status seemed to have played a role in modality choice, but the majority was still treated with microsurgery. Stent-assisted coiling appears to have comparable safety in unruptured cases but with greater technical difficulty at this specific location. Though flow-diversion is feasible, it seems to carry a higher risk of ischemic events and delayed rupture at the MCA bifurcation. In ruptured cases, SAC and FDr had a high rate of periprocedural thromboembolic complications. In spite of that, in-hospital mortality did not seem to be different among treatments regardless of rupture status. Better angiographic results and lower retreatment rates were achieved with MC. Disclosures: A. Monteiro: None. W. Khawar: None. L. Kim: None. M. Levitt: None. G. Barros: None. A. Boulos: None. A. Paul: None. P. Jabbour: None. K. El Naamani: None. R. Nogueira: None. D. Haussen: None. A. Al Bayati: None. M. Mohammaden: None. T. Jovin: None. J. Khalife: None. P. Kan: None. M. Colasurdo: None. M. McGrath: None. C. Ross: None. M. Yeradi: None. M. Devaraju: None. I. Stafstrom: None. A. Baig: None. M. Waqas: None. J. Cappuzzo: None. E. Levy: 2; C; Claret Medical, GLG Consulting, Guidepoint Global, Imperial Care, Medtronic, Rebound, StimMed, Misionix, Mosiac, Clarion, IRRAS. 4; C; NeXtGen Biologics, RAPID Medical, Claret Medical, Cognition Medical, Imperative Care, Rebound Therapeutics, StimMed, Three Rivers Medical.. 6; C; Reimbursement for travel and food for some meetings with the CNS and ABNS. A. Siddiqui: 2; C; Amnis Therapeutics, Apellis Pharmaceuticals, Inc., Boston Scientific, Canon Medical Systems USA, Inc., Cardinal Health 200, LLC, Cerebrotech Medical Systems, Inc., Cerenovus, Cerevatech Medical, Inc., . 4; C; Adona Medical, Inc., Amnis Therapeutics, Bend IT Technologies, Ltd., BlinkTBI, Inc, Buffalo Technology Partners, Inc., Cardinal Consultants, LLC, Cerebrotech Medical Systems, Inc, Cerevatech Medical,